0587 Arousal During Sleep Is Associated With Hypertension In Obstructive Sleep Apnea. (12th April 2019) - Zhang, Ye; Ren, Rong; Yang, Linghui; Tan, Lu; Tang, Xiangdong
Abstract: Introduction: Repetitive asphyxia events in obstructive sleep apnea (OSA) result in brain arousal, intermittent hypoxemia, and increased sympathetic nervous system activity, which is associated with sleep fragmentation. Arousal index could reflect the severity of sleep fragmentation. In normal humans, arousal which is associated with sympathetic hyperactivity results in transient increases in blood pressure. However, the association of arousal during sleep with hypertension has not been explored in OSA. Methods: A total of 11, 218 patients with apnea-hypopnea index (AHI) ≥ 5/h were included in this study (83.7% males, mean age = 45.06 ± 12.05 years). All patients underwent an overnight PSG. OSA patients were divided into four groups based on the interquartile of arousal index (<18.40 (n=2822), 18.40-30.85 (n=2787), 30.85-49.5 (n=2807), and >49.5 (n=2802)). Hypertension was defined based either on direct blood pressure measures or on diagnosis by a physician. Linear and logistic regression models were used to estimate the associations between arousal index and hypertension prevalence in OSA. Results: Logistical regression analysis revealed that OSA combined with arousal index > 49.5 increased the odds of hypertension by 18.1% (odds ratio, 1.181; 95% confidence interval, 1.024-1.360) compared with OSA patients combined with arousal index < 18.40. Multiple linear regression analysis revealed that arousal index was significantly positive associated with systolic blood pressure (β= 0.039, p<0.001) and diastolic blood pressure (β= 0.059, p<0.001) in OSA. These results were independent of major confounding factors such as sex, age, body mass index, tobacco, alcohol drinking, coffee use, sleep efficiency and subjective daytime sleepiness, OSA severity and nocturnal oxygen desaturation. Conclusion: We conclude that an increased arousal index is associated with hypertension in OSA patients, indicating that sleep fragmentation in OSA may actually be detrimental in terms of hypertension risk. Support (If Any): This work was supported by the National Natural Science Foundation of China (81530002 81770087).